Evolocumab on top of empagliflozin improves endothelial function of individuals with diabetes: randomized active-controlled trial - Andrei C. Sposito; Ikaro Breder; Joaquim Barreto; Jessica Breder; Isabella Bonilha; Marcus Lima; Alessandra Oliveira; Vaneza Wolf; Beatriz Luchiari; Helison R. do Carmo; Daniel Munhoz; Daniela Oliveira; et al. (Cardiovascular Diabetology, 2022)
Abstract Background Sodium-glucose cotransporter 2 inhibitors (SGLT2i) improve endothelial dysfunction and reduce cardiovascular events in individuals with type 2 diabetes (T2D). Proprotein convertase subtilisin/kexin 9 (PCSK9i) inhibitors reduce cardiovascular events in high-risk patients. Whether the addition of PCSK9i to SGLT2i treatment adds benefits is not known. Objectives To assess the PCSK9-i effect on the endothelial function of T2D individuals under treatment with SGLT2-i. Methods Individuals with T2D were randomized in a 1:1 ratio to a 16-week treatment with either empagliflozin (E) or empagliflozin plus evolocumab (EE). The primary endpoint was post-treatment change from baseline in flow-mediated dilation (FMD) at 1-min. Secondary outcomes included changes in plasma levels of nitric oxide metabolites and isoprostane. Results A total of 110 patients were enrolled, the mean age was 58 years, and 71% were men. The median post-treatment change in FMD at 1-min was 2.7% (interquartile range [IQR]: 0.9%) and 0.4% (IQR: 0.9%) in the EE and E groups, respectively (p < 0.001). There was a greater increase in plasma levels of nitrate [5.9 (16.5) vs. 2.6 (11.8); p = 0.001] and nitrite [0.14 (0.72) vs. 0.02 (0.74); p = 0.025] in the EE group than in the E group, respectively. Isoprostane reduction was more pronounced in the EE group when compared to the E group [−1.7 (5.9) vs. −1.1 (5.3); p < 0.001). Conclusions In individuals with T2D, the addition of evolocumab on top of empagliflozin improves endothelial function.